El nuevo sentido de un espacio colectivo. El mercado de La Boqueria de Barcelona - Steegman, David (E|C, 2020)
Markets in cities around the world, especially those located in the most visited urban centers, are experiencing profound changes, both in the nature of the food supply and in relation to the forms of use by citizens. Straddling the supermarket, the mall and the restaurant, often superimposed on the traditional market, our time is giving birth to a new business model considerably far removed from the original function of supplying fresh food to the urban population. Located in the Ciutat Vella area, in Barcelona, in the heart of the area of the city with a greater tourist pressure, a part increasingly dedicated to leisure and gastronomy, the Boqueria market is an example worth observing carefully. The opening of more and more food stalls, usually to take away, and the sale of snacks as a complement to the business of traditional stalls, are giving this space an environment that is increasingly different from that of a traditional food market. In La Boqueria, as well as in other central markets of the city, the emergence of this new model is not only related to the influence of tourism, but also to profound changes in the food dynamics and lifestyles of the local population, in turn linked to important social, demographic and economic transformations.